Development of a qPCR for Leifsonia xyli subsp. xyli and quantification of the effects of heat treatment of sugarcane cuttings on Lxx. (February 2016) - Carvalho, G.; da Silva, T.G.E.R.; Munhoz, A.T.; Monteiro-Vitorello, C.B.; Azevedo, R.A.; Melotto, M.; Camargo, L.E.A.
Abstract: The main control practice of Leifsonia xyli subsp. xyli (Lxx) in sugarcane is to heat-treat cane cuttings used as planting material in an attempt to eradicate the bacterium. A real time quantitative PCR (qPCR) protocol specific for Lxx was developed to assess the effectiveness of this practice. Primers were designed from the sequence of an Lxx-specific gene and detected as few as 10 −5  ng of Lxx DNA in 100 ng of plant DNA. Two experiments were conducted to quantify Lxx titers in plants of the varieties SP80-3280 and SP70-3370 originated from cuttings treated or not by immersion in hot water at 52 °C for 30 min. In the first experiment, cuttings were collected from plant canes with low Lxx titers whereas in the second they were collected from first-ratoon canes with higher titers. Lxx was quantified in leaves by qPCR 90 days after planting and was detected in 50–90% of the plants at variable titers, indicating that the 52 °C hot water treatment for 30 min was not effective in eradicating Lxx from all plants. However, in the second experiment the bacterial population was reduced, as the median number of Lxx cells was lower compared to the non-treated control. In the case of SP70-3370, the treatment also reduced the number of Lxx-infected plants considering the pooled data of the two experiments. The results indicated that although the 52 °C hot water treatment for 30 min did not completely eliminate Lxx, it can be used to reduce the pathogen population in plants propagated from canes with high Lxx titers Highlights: Heat treatment is used to control Leifsonia xyli subsp. xyli (Lxx)in sugarcane cuttings. A qPCR protocol was developed to quantify Lxx. The treatment was ineffective in eliminating Lxx from cuttings. The treatment reduced the levels of Lxx in plants of cuttings taken from canes with high bacterial populations.